CRAN-08. NATIONAL UK GUIDELINES FOR THE INVESTIGATION, TREATMENT AND LONG-TERM FOLLOW-UP OF PAEDIATRIC CRANIOPHARYNGIOMA. Issue 2 (22nd June 2018) - Gan, Hoong-Wei; Aquilina, Kristian; Morillon, Paul; Albanese, Assunta; Barkas, Konstantinos; Chandler, Chris; Chang, Yen-Ching; Daousi, Christina; Drimtzias, Evangelos; Farndon, Sarah; Jacques, Tom; Korbonits, Marta; et al.
Abstract: BACKGROUND: Craniopharyngiomas are the commonest suprasellar tumour in childhood. Despite high overall survival, children with craniopharyngiomas are at risk of multiple relapses and long-term tumour- and treatment-related morbidity. We sought to provide, for the first time, a national evidence-based standard for best practice for the assessment, treatment, and follow-up of paediatric craniopharyngiomas. METHODS: 44 clinical questions were formulated based on a PICO (Population, Intervention, Comparison, Outcome) format by a multidisciplinary Guideline Development Group to guide systematic searches via the Ovid MEDLINE (1946-February 2017) and Cochrane Library (2016, Issue 12) databases, identifying 2023 separate research articles. Publications underwent a three-tier filtering process and 300 were reviewed using the GRADE approach. Where recommendations could not be made, a two-stage international Delphi consensus process was conducted. RESULTS: 35 recommendations were made, largely based on low to very low quality evidence. 30 further recommendations achieved >70% agreement via Delphi consensus. Craniopharyngiomas should be managed in tertiary paediatric centres with sufficient neuro-oncology, neurosurgery, endocrinology, radiology, pathology and neuropsychology experience. At diagnosis, tumours should be graded using the "Paris" grading system and surgical treatment tailored to avoid hypothalamic damage, with adjuvant radiotherapy being offered after incomplete resections. Recommendations on the long-term multidisciplinary follow-up of survivors are also detailed. CONCLUSIONS: These Royal College of Paediatrics and Child Health (RCPCH)-endorsed guidelines provide the first evidence-based national recommendations for the management of paediatric craniopharyngioma. Through their implementation, we hope to achieve better consistency in the quality of care of such patients and improve long-term quality of survival.